2017
DOI: 10.1080/14756366.2017.1355793
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric inhibition of carnosinase (CN1) by inducing a conformational shift

Abstract: In humans, low serum carnosinase (CN1) activity protects patients with type 2 diabetes from diabetic nephropathy. We now characterized the interaction of thiol-containing compounds with CN1 cysteine residue at position 102, which is important for CN1 activity. Reduced glutathione (GSH), N-acetylcysteine and cysteine (3.2 ± 0.4, 2.0 ± 0.3, 1.6 ± 0.2 µmol/mg/h/mM; p < .05) lowered dose-dependently recombinant CN1 (rCN1) efficiency (5.2 ± 0.2 µmol/mg/h/mM) and normalized increased CN1 activity renal tissue sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…GPx4 het mice are particularly susceptible to increased RCS, because GPX4 is obligatory for neutralizing lipid peroxides in cell membranes and circulating lipoproteins. In both fructose-fed (10). Further, the novel agent carnostatine (SAN9812) was shown to be a potent and selective carnosinase inhibitor in animal models (11).…”
Section: Considerations and Future Directionsmentioning
confidence: 99%
“…GPx4 het mice are particularly susceptible to increased RCS, because GPX4 is obligatory for neutralizing lipid peroxides in cell membranes and circulating lipoproteins. In both fructose-fed (10). Further, the novel agent carnostatine (SAN9812) was shown to be a potent and selective carnosinase inhibitor in animal models (11).…”
Section: Considerations and Future Directionsmentioning
confidence: 99%
“…With regard to carnosinase recognition, docking simulations were based on the already reported putative complex between carnosine and carnosinase and were carried out by adopting the computational strategies previously described (Peters et al 2017). Similarly, docking simulations on PEPT1, the transporter responsible for dipeptide transport across intestinal enterocytes, involved the homology model as generated by fragments (Pedretti et al 2008) and were based on the computational procedures reported elsewhere (Vistoli et al 2012).…”
Section: Molecular Modellingmentioning
confidence: 99%
“…Furthermore, an enzyme β-ala-his dipeptidase (CNDP1), or better known as serum carnosinase, also showed changes in expression in serum proteome of patients after transplantation. Many previous researches have focused on the association of this gene with human diabetic nephropathy [78][79][80] . It was demonstrated that low carnosinase activity has a protective effect against adverse effects of high glucose levels on kidney, resulted from an increase of carnosine in blood 81 .…”
Section: Discussionmentioning
confidence: 99%